Visualising future behaviour: Effects for snacking on biscuit bars, but no effects for snacking on fruit. (August 2015) - Adams, Catherine; Rennie, Laura; Uskul, Ayse K; Appleton, Katherine M
In this study, participants ( N = 223) were randomised to visualise snacking on fruit, visualise snacking on biscuit bars or no visualisation, and intentions and attitudes towards fruit and biscuit bars, immediate selection of fruit or biscuit bars and subsequent consumption were measured. No effects of visualising snacking on fruit were found once background variables were taken into account. Visualising snacking on biscuit bars, however, resulted in greater intentions to consume biscuit bars (smallest β = 0.19, p < 0.01). These findings suggest that specifics of the visualised target behaviour may be important in visualisation. Further investigation is needed before recommending visualisation for increasing fruit consumption.